Evaluating the impact of an information-based education and training platform on the incidence, severity, and coping resources status of workplace violence among nurses: a quasi-experimental study - Ying Zhang; Jianzheng Cai; Ziyu Qin; Haifang Wang; Xiuying Hu (BMC, 2023)
Abstract Background Workplace violence among nurses has emerged as a critical issue, posing a significant threat to their occupational safety. Education and training are the primary measures employed to prevent and respond to workplace violence. However, the current approaches have proven ineffective, possibly due to a lack of consideration for the specific needs of clinical nurses. Therefore, it is essential to explore the effectiveness of an informational education and training platform tailored to nurses' requirements. This study aimed to investigate the impact of such a platform on the incidence, severity, and coping resources of WPV in nurses. Methods This research was a quasi-experimental study. An information-based education and training platform focused on nurse workplace violence was developed through literature reviews, expert meetings, consultations with software development companies, and a trial run. A tertiary general hospital in Suzhou was selected, in which hospital district A was the intervention group and hospital district B was the control group. A total of 276 nurses were recruited, 140 in the intervention group and 136 in the control group. The nurses' incidence, severity, coping resources status, and evaluation of the application were measured before the intervention and at 1, 3, and 6 months after the intervention. Results The overall incidence of workplace violence, verbal aggression, and verbal threat among nurses showed statistically significant differences (P < 0.05) for the time effect, while the incidence of physical aggression demonstrated statistically significant differences (P < 0.05) for the between-group effect and the time effect. The severity of physical violence among nurses exhibited statistically significant differences (P < 0.05) for the between-group effect and time effect, and the severity of psychological violence showed statistically significant differences (P < 0.05) for the time effect. Nurses' total coping resources score and dimensions also showed statistically significant differences in terms of group, time, and interaction effects (P < 0.001). The evaluation questionnaire for the mobile application indicated usefulness scores of 2 (1, 2); ease of learning scores of 2 (1, 2); ease of use scores of 2 (1, 2); trust scores of 2 (1, 2.75); acceptance score of 1 (1, 2); and satisfaction scores of 2 (1, 2). Conclusions Implementing the nurse workplace violence information-based education and training platform proved beneficial in reducing the incidence and severity of workplace violence among nurses and enhancing their coping resources. This outcome suggested the platform's potential for further application and promotion in clinical settings.